Noninvasive Estimation of Aortic Stiffness Through Different Approaches: Comparison With Intra-Aortic Recordings. Issue 1 (July 2019) - Salvi, Paolo; Scalise, Filippo; Rovina, Matteo; Moretti, Francesco; Salvi, Lucia; Grillo, Andrea; Gao, Lan; Baldi, Corrado; Faini, Andrea; Furlanis, Giulia; Sorropago, Antonio; Millasseau, Sandrine C.; et al.
Abstract : Aortic pulse wave velocity is a worldwide accepted index to evaluate aortic stiffness and can be assessed noninvasively by several methods. This study sought to determine if commonly used noninvasive devices can all accurately estimate aortic pulse wave velocity. Pulse wave velocity was estimated in 102 patients (aged 65±13 years) undergoing diagnostic coronary angiography with 7 noninvasive devices and compared with invasive aortic pulse wave velocity. Devices evaluating carotid-femoral pulse wave velocity (Complior Analyse, PulsePen ET, PulsePen ETT, and SphygmoCor) showed a strong agreement between each other ( r >0.83) and with invasive aortic pulse wave velocity. The mean difference ±SD with the invasive pulse wave velocity was −0.73±2.83 m/s ( r =0.64) for Complior-Analyse: 0.20±2.54 m/s ( r =0.71) for PulsePen-ETT: −0.04±2.33 m/s ( r =0.78) for PulsePen ET; and −0.61±2.57 m/s ( r =0.70) for SphygmoCor. The finger-toe pulse wave velocity, evaluated by pOpmètre, showed only a weak relationship with invasive aortic recording (mean difference ±SD =−0.44±4.44 m/s; r =0.41), and with noninvasive carotid-femoral pulse wave velocity measurements ( r <0.33). Pulse wave velocity estimated through a proprietary algorithm by BPLab (v.5.03 and v.6.02) and Mobil-O-Graph showed a weaker agreement with invasive pulse wave velocity compared with carotid-femoral pulse wave velocity (mean difference ±SD =−0.71±3.55 m/s, r =0.23; 1.04±2.27 m/s, r =0.77; and −1.01±2.54 m/s, r =0.71, respectively), revealing a negative proportional bias at Bland-Altman plot. Aortic pulse wave velocity values provided by BPLab and Mobil-O-Graph were entirely dependent on age-squared and peripheral systolic blood pressure (cumulative r 2 =0.98 and 0.99, respectively). Thus, among the methods evaluated, only those assessing carotid-femoral pulse wave velocity (Complior Analyse, PulsePen ETT, PulsePen ET, and SphygmoCor) appear to be reliable approaches for estimation of aortic stiffness. Abstract : Supplemental Digital Content is available in the text.